Polarized politics of pandemic response and the Covid-19 connectedness across the U.S. states - Umut Akovalı; Kamil Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
This paper investigates the state-level differences in government and community responses to the Covid-19 pandemic, leading to different growth trajectories of Covid-19 cases and their connectedness across the U.S. states. Our regression analysis shows that higher growth trajectories are observed in the states that implemented the lax government and community response to the pandemic. Moving to the analysis of spillovers/connectedness of Covid-19 cases across the states, we apply the Diebold-Yilmaz connectedness methodology to the growth rates of Covid-19 cases. Using the total directional connectedness measures, we find that the states with lax government and community response generated connectedness of Covid-19 cases to others. These findings are also supported by the secondary regression analysis of pairwise connectedness measures over time. Finally, the travel intensity between the pairs of states, indirectly measured by the data on smartphone location exposure, contributes significantly to the pairwise directional connectedness of Covid-19 across the states.
Keywords: I10; I18; 330; Covid-19; Coronavirus; Spillovers; Connectedness; Government policy stringency; Community mobility; Travel Intensity